International migration in the presence of public goods - Nadine Leiner (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1995)
The paper analyses the effects of international migration on national welfare and on the structure of private production in a two-country trade model with public goods. Implications for migration policy and the role and design of entrance fees are discussed. It is further demonstrated that a migration-induced adjustment in public good supply affects a country's trade structure: in a Heckscher-Ohlin framework an immigration (emigration) of labourers can be connected to a decrease (increase) in the production of the labour intensive private good.
Keywords: 330; migration; public goods; international trade